Wine tourism in an agritourism context: insight into agritourism providers’ perceptions - Dimitrovski, Darko (2017)
Rural regions abounding in vineyards provide a perfect setting for blending wine and agricultural tourism. Both types of tourism offer a varied combination of heterogeneous agricultural products and experiences, which add value to rural regions. In this article, wine tourism is described as part of a wider agritourism phenomenon. We start with a brief summary of an extensive literature review of the concepts of ‘wine tourism’ and ‘agritourism’. Some of the key themes resulting from this reading exercise were then confronted with the reality in the Vila Real district. Six in-depth interviews were conducted with the managers of accommodation units, which are officially categorised as agritourism units. Thus, a first set of data was collected which will allow a better understanding of the place of wine and agritourism in that area, which partially integrates the Demarcated Douro Wine Region. In other words, the supply side was analysed by comparing what happens in the Vila Real district with global widespread practices concerning the following topics: What are the main motivations of the managers, how do they perceive agritourism’s benefits, what are their attitudes towards heritage preservation and how do they profile the agritourism visitors? The research results will increase insight into the agritourism reality and allow us to formulate valuable guidelines for the future development of the sector.